2013
DOI: 10.6007/ijarbss/v3-i11/375
|View full text |Cite
|
Sign up to set email alerts
|

Perception on Lean Practices in a Lean Implementation

Abstract: In today's highly competitive world where most businesses focus on cost and quality, organizations with efficient and effective supply chains are able to stand out with inherent competitive advantages. To achieve this many organizations adopt lean practices which fundamentally stress on the elimination of non-value added tasks (such as unwanted transportation, extra processing, excess motion, repairs on defects, over production, excess inventory and incidents of waiting or delays). Nevertheless, the introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In contrast to critical studies on Lean, Oon (2013) studied worker perception in a Japaneseowned company operating outside of Japan and found that employees who had training and exposure to Lean Principles view internal performance more favorably than employees who had not been trained in or exposed to the Lean Principles. The difference between these findings and previous studies suggests that how Lean is implemented affects how it is viewed by employees.…”
Section: Employee Perceptionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to critical studies on Lean, Oon (2013) studied worker perception in a Japaneseowned company operating outside of Japan and found that employees who had training and exposure to Lean Principles view internal performance more favorably than employees who had not been trained in or exposed to the Lean Principles. The difference between these findings and previous studies suggests that how Lean is implemented affects how it is viewed by employees.…”
Section: Employee Perceptionmentioning
confidence: 90%
“…Multiple researchers have made the point that a company is only as "Lean" as their employees perceive them to be (Jayamaha et al, 2014;Losonci et al, 2011;Oon, 2013;Shadur et al, 1995;Shetty, 2011). If employees believe that Lean characteristics are not present in the organization it would suggest that a culture of continuous improvement and respect for people has not been established (Shetty, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that it would be difficult to adopt lean without understanding the employee perspective, and a manufacturing organization is only as lean as its employees perceive it to be (Losonci et al , 2011; Oon, 2013; Lodgaard et al , 2016; Shadur et al , 1995; Jayamaha et al , 2014; Shetty, 2011; Loyd, 2018). At a Hungarian auto parts plant, Losonci et al (2011) found that the employee's beliefs, commitment to company, communication and work method were main contributors to lean.…”
Section: Introductionmentioning
confidence: 99%
“…At a Hungarian auto parts plant, Losonci et al (2011) found that the employee's beliefs, commitment to company, communication and work method were main contributors to lean. Oon (2013) conducted a survey to study employee perception at a semiconductor company in Malaysia and found differences between workers with significant exposure to lean principles and those without. Lodgaard et al (2016) conducted a two-year study in a Norway manufacturing company and found differences in perception of barriers to continuous improvement between hierarchical levels of employees.…”
Section: Introductionmentioning
confidence: 99%